PENGARUH PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA (Studi Pada Desa Di Kecamatan Malua, Kabupaten Enrekang) - Ilham, Surianto; Al-Qadri, Muhammad Syarif; Timpa, Hasmawati; Nisa, Iien Rohmatun; S, Muh. Sukran (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the impact of internal control systems on fraud prevention in village fund management. The approach implemented in this research is quantitative, employing simple linear regression analysis. Data were obtained through questionnaires distributed to seven villages in Malua District, Enrekang Regency. The research findings reveal that internal control has a significant impact on fraud prevention. These results indicate that implementing an effective internal control system can be a key strategy to minimize the risk of fraud while supporting more transparent and accountable village fund management. This research emphasizes the importance of strengthening internal control mechanisms to protect public resources and increase transparency in village governance.